2017
DOI: 10.1126/scisignal.aam9563
|View full text |Cite
|
Sign up to set email alerts
|

Altered homeostasis and development of regulatory T cell subsets represent an IL-2R–dependent risk for diabetes in NOD mice

Abstract: The cytokine interleukin-2 (IL-2) is critical for the functions of regulatory T cells (T). The contribution of polymorphisms in the gene encoding the IL-2 receptor α subunit (), which are associated with type 1 diabetes, is difficult to determine because autoimmunity depends on variations in multiple genes, where the contribution of any one gene product is small. We investigated the mechanisms whereby a modest reduction in IL-2R signaling selectively in T lymphocytes influenced the development of diabetes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 70 publications
0
6
0
2
Order By: Relevance
“…To assess diabetes in NOD mice, urine and blood glucose levels were monitored at least twice a week; mice were considered diabetes when blood glucose levels were >250 mg/dl. Pancreas lymphoid cells from NOD mice were prepared as previously described (40).…”
Section: Methodsmentioning
confidence: 99%
“…To assess diabetes in NOD mice, urine and blood glucose levels were monitored at least twice a week; mice were considered diabetes when blood glucose levels were >250 mg/dl. Pancreas lymphoid cells from NOD mice were prepared as previously described (40).…”
Section: Methodsmentioning
confidence: 99%
“…IL-2 is critical for Treg development and function, as IL-2Rα KO, IL-2Rβ KO, and neutralization of IL-2 induce severe autoimmunity [87][88][89] . Very recent reports by Dwyer et al have further revealed that the level of IL-2 signaling is vital to proper Treg function, as chronically reduced IL-2 signaling compromised peripheral tolerance and led to accelerated onset of type 1 diabetes in NOD mice 90 . Despite its necessity for function, CD25 is not exclusively on Tregs and does not mark the Treg population as effectively in humans as it does in mice.…”
Section: Differentiation and Functionmentioning
confidence: 99%
“…5 C ). Although the initial break in tolerance in type 1 diabetes seems to be due in part to defects in the Treg cell compartment, there is also evidence that the Teff cells are resistant to regulation (21) and that even a minor reduction in Treg cells due to reduced interleukin-2Rβ signaling is enough to accelerate diabetes onset (22), suggesting that reducing Teff cells may be the most effective strategy in attempting to reverse new-onset disease. This is supported by a recent study (23) showing protection from disease development in NOD mice due to gut metabolite-induced changes, either reducing the autoreactive Teff cell compartment or augmenting the Treg cell compartment, although each independently provided protection from disease, the diet that reduced the autoreactive Teff cells showed greater efficacy.…”
Section: Discussionmentioning
confidence: 99%